Reinjury Following Return to Play - Watts V, George J.; Tai, Ryan; Joshi, Ganesh; Garwood, Elisabeth; Saha, Debajyoti (Seminars in Musculoskeletal Radiology, 2024)
Radiologists are frequently called on for guidance regarding return to play (RTP) for athletes and active individuals after sustaining a musculoskeletal injury. Avoidance of reinjury is of particular importance throughout the rehabilitative process and following resumption of competitive activity. Understanding reinjury risk estimation, imaging patterns, and correlation of clinical and surgical findings will help prepare the radiologist to identify reinjuries correctly on diagnostic imaging studies and optimize management for a safe RTP.
Keywords: reinjury; magnetic resonance imaging; hamstrings; anterior cruciate ligament